Tailoring the surface-oxygen defects of a tin dioxide support towards an enhanced electrocatalytic performance of platinum nanoparticles. Issue 8 (9th September 2015) - Manikandan, Maidhily; Tanabe, Toyokazu; Ramesh, Gubbala V.; Kodiyath, Rajesh; Ueda, Shigenori; Sakuma, Yoshiki; Homma, Yusaku; Dakshanamoorthy, Arivuoli; Ariga, Katsuhiko; Abe, Hideki
Abstract : Tin-dioxide nanofacets with long-range ordered surface-oxygen defects exhibit an enhanced electrocatalytic performance due to the promoted charge transport at the metal–semiconductor interface. Abstract : Tin-dioxide nanofacets (SnO2 NFs) are crystal-engineered so that oxygen defects on the maximal {113} surface are long-range ordered to give rise to a non-occupied defect band (DB) in the bandgap. SnO2 NFs-supported platinum-nanoparticles exhibit an enhanced ethanol-electrooxidation activity due to the promoted charge-transport via the DB at the metal–semiconductor interface.